Efektivitas Pelatihan Asertif terhadap Penurunan Kecemasan Berbicara di Depan Umum pada Mahasiswa - Andi Ahmad Arif; Sitti Murdiana; Ahmad Ridfah (Humanitas (Jurnal Psikologi), 2024)
This aims of this study are to determine the effectiveness of an assertive training to reducing public speaking anxiety among students psychology department, Universitas Negeri Makassar. Participants in this study is 20 student was obtained and was further divided into two group: experimental and control group. This study used  a true experiment design  with pretest-posttest control group design. The data analysis technique used is  the Mann Whitney test  to see the difference between the experimental group and the control group. The results of the Mann Whitney  test show asymp values. Sig. (1-tailed) which is 0.00 < 0.05. It can be concluded that assertive training is effective for lowering public speaking anxiety in college students. Assertive training is proven to be able to make individuals think more positively, have a good self-concept, and have skills for public speaking so as to reduce the level of anxiety in public speaking in students of the Psychology department, Universitas Negeri Makassar.